Answer:
the last one i think
Step-by-step explanation:
Answer:1/3 i dont know if this is right i just kindly copied the guy on top
Step-by-step explanation:
Answer:
C. 4x = 12
Step-by-step explanation:
You and three friends= you + 3 friends=4 people
Pizza= 12 pieces
Each person eats equal pieces of pizza
x= number of pieces each person ate
Equation
4x=12
Divide both sides by 4
x=12/4
=3
x=3
Therefore, each person ate 3 pieces of pizza each
Check:
4x=12
4(3)=12
12=12
The commutative property states that you can invert the order of the terms of a sum:
![a+b=b+a](https://tex.z-dn.net/?f=a%2Bb%3Db%2Ba)
So, if you start with
![\dfrac{1}{3}+\dfrac{2}{5}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B3%7D%2B%5Cdfrac%7B2%7D%7B5%7D)
Applying the commutative property you'll get
![\dfrac{2}{5}+\dfrac{1}{3}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%7D%7B5%7D%2B%5Cdfrac%7B1%7D%7B3%7D)